Numerical investigation of losses in a double-suction multistage centrifugal pump and its mitigation using baffle plates - Shamsuddeen, Mohamed Murshid; Kim, Sung; Shahzer, Mohammad Abu; Ma, Sang-Bum; Kim, Jin-Hyuk (Frontiers in Energy Research, 2022)
The flow in a double-suction twin-volute five-stage centrifugal pump is studied numerically using Computational Fluid Dynamics (CFD) calculations. The pump performance at various flow rates obtained numerically are compared with the theoretically results. The deterioration in pump performance at various flow rates were investigated to find the losses associated with the design of the pump components. The stage-wise performance analysis revealed the hydraulic losses associated with the second-stage impeller due to highly swirled flow exiting from the first stage twin-volute. The fluid exiting the twin-volute have a high circumferential velocity than its radial component leading to a high pre-swirl at the inlet of stage 2 impeller. In order to regulate the high pre-swirl, baffle plates were installed at the exit of the twin-volute. Three baffle plate configurations were studied and their effects on the pump performances were compared. The vertical configuration improved the pump efficiency by 1.36% and head by 6.04% while the horizontal configuration improved them by 2.42% and 5.96% respectively. The 4-plate baffle configuration improved the pump performance by only a small margin. The installation of the baffle plates also improved the stage performances in both design and off-design conditions. The horizontally installed baffle plates were then tested at various angles. The plates installed at 300° clock-wise increased the pump head by 9.08% and efficiency by 3.87%. A comprehensive analysis of the flow physics inside the pump are also presented.